Relationship between Knowledge and Family Support with pregnant women's Antenatal Care (ANC) Compliance - Berliana Irianti; Nelly Karlinah (Institute of Computer Science (IOCS), 2021)
One indicator of the success of maternal health efforts is the Maternal Mortality Rate (MMR). Indonesia is still far from the SDG target of 305 per 100,000 live births, is in 2030. Antenatal care can help to reduce the high risk of maternal death during pregnancy. The ideal K1 and K4 indicators, which refer to the frequency and trimester during which ANC is performed, indicated that health checks should continue during pregnancy. Busyness, knowledge, attitude, low socioeconomic level, lack of husband's support, lack of maternal services facilities, poor medical care, and lack of trained personnel are all factors that makes pregnant women less motivated to do antenatal care. The study was conducted In June - July 2021, 32 pregnant women have been used as samples in this study. The research is descriptive with a cross-sectional design. The chi square statistic is being used in the study. It was discovered that maternal knowledge and antenatal care adherence have a significant relationship, Statistical results show P-value is 0.002. Additionally, there is a relationship between family support and antenatal care compliance. P-value is 0.000 is statistical result. .